Green Star Auto Enterprise Car Selling System - TANG, SHIUAN LIANG; Abdullah, Noryusliza (Applied Information Technology And Computer Science, 2025)
The Green Star Auto Enterprise Car Selling System is a web-based solution aimed in enhancing the sales process by systematizing and streamlining operations. Green Star Auto Enterprise faces challenges in effectively marketing and reaching potential buyers within the highly competitive used car market. The purpose of developing this system is to address the specific issues encountered by Green Star Auto Enterprise. The proposed system is developed using the waterfall methodology involving requirements gather, design, implementation, verification and maintenance phases. Key findings highlight the significance of a transparent vehicle history presentation and trends show a growing preference for cost-effectiveness compact car. The Car Selling System is expected to enhance the enterprise's market reach, reduce time consumption, increase the efficiency of the selling process, and provide a secure transaction platform.